Design Thinking-based Adaptive Web Learning System for Science Education with Visual and Verbal Learning Modes - Arief Rahman Hakim; I Nyoman Sudana Degeng; Waras Kamdi; Yerry Soepriyanto (Online Learning In Educational Research (OLER), 2025)
Accommodating diverse learning styles remains a challenge in science education. This pilot study used a one-group pretest–posttest design to develop and evaluate a web-based adaptive learning system for 5th-grade science students (n = 27) at SDN Bumiayu 3 Malang (State Elementary School of Bumiayu 3 Malang). The system assigned students to either visual or verbal instructional modes based on an initial questionnaire. Development followed the design thinking phases: empathize, define, ideate, prototype, and test. Effectiveness was measured using a 20-item multiple-choice test administered before and after a one-month intervention. The average score increased from 37.00 (SD = 9.42) to 77.33 (SD = 8.55), with an N-Gain of 0.61, indicating moderate improvement. These findings suggest that web-based adaptive systems tailored to specific learning modes can enhance students’ science understanding and learning outcomes. This research provides practical insights for the broader implementation of customized digital learning tools to meet diverse student needs in similar educational settings